2013
DOI: 10.1177/016264341302800404
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the iPad into Language Arts Instruction for Students with Disabilities: Engagement and Perspectives

Abstract: This preliminary mixed method single subject and qualitative interview study explored the incorporation of iPad tablets into the language arts lessons of four elementary school students with language-based disabilities. Using the iPad increased the student's academic engagement, which was measured by monitoring the number of prompts required to keep the students on task. Teacher and student interviews revealed high levels of satisfaction with using the iPad for language arts instruction. These findings confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 3 publications
2
31
0
Order By: Relevance
“…Respondents indicated using iPads for a range of instructional purposes in their classrooms and share that the iPad is supportive in engaging and motivating students who have a range of diverse learning support needs. This supports the findings of Hewett, Torgerson, and Douglas () and Cumming and Draper Rodriguez (). Respondents reported using iPads in their classrooms to support learners’ communication skills including easy access to symbols and using the iPad as a communications book, which extends the work of Backes and Geradsschmidt () who showed how the iPad is an accessible voice generating tool.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Respondents indicated using iPads for a range of instructional purposes in their classrooms and share that the iPad is supportive in engaging and motivating students who have a range of diverse learning support needs. This supports the findings of Hewett, Torgerson, and Douglas () and Cumming and Draper Rodriguez (). Respondents reported using iPads in their classrooms to support learners’ communication skills including easy access to symbols and using the iPad as a communications book, which extends the work of Backes and Geradsschmidt () who showed how the iPad is an accessible voice generating tool.…”
Section: Discussionsupporting
confidence: 90%
“…Many students with diverse learning needs benefit from, indeed require, technology to 'assist' them to access the curriculum, participate in learning activities, produce learning products, and achieve success in the classroom (Hopkins, 2004;Philips and Schweisfurth, 2014). Traditional technology to support children with diverse needs is often expensive, cumbersome, stigmatising, and time-consuming to program and personalise (Cumming and Draper Rodriguez, 2013). Merbler, Hadadian and Ulman (1999) made a case for using assistive technology to support students with disabilities in inclusive classrooms over a decade ago.…”
Section: Why the Ipad?mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is necessary to compare the results of this study to existing educational research involving mobile technology. Such research has generally concluded that instruction supported with mobile technology is associated with increased engagement and improved academic outcomes (Chiong and Shuler 2010;Cumming and Draper Rodriguez 2013;Fishburn 2009;Getting and Swainey 2012;Hutchison et al 2012;McClanahan et al 2012;Shuler 2009). For example, in their use of iPads with their Tier 2 and 3 classroom reading groups, Getting and Swainey (2012) observed increases in the students' time on-task behavior over the course of the school year.…”
Section: Discussionmentioning
confidence: 99%
“…Getting and Swainey (2012) used iPads with their lowest first grade reading groups for two consecutive school years, which resulted in elevated average gains and/or higher end-of-year reading scores for students with routine iPad use, and 15-20 % average increases in time on-task across observations. Further evidence from exploratory case studies found that the use of iPad applications targeting specific reading skills increased task engagement (Cumming and Draper Rodriguez 2013) and improved reading skills (McClanahan et al 2012).…”
Section: Effects Of Educational Technology On Reading and Engagement mentioning
confidence: 99%